Structural Types of Speech Acts with the Explicit Mode of Belief and their Expressive Properties in Scientific Dialogue - O. N. Chalova (Дискурс)
Introduction. The article is about identifying structural and pragmatic features of references to belief presented in scientific dialogue that involves the verbal interaction of scientists and develops in a spontaneous way at a scientific forum of any format in order to discuss and solve a scientific problem. The relevance of the analysis is predetermined by a number of factors: the focus of modern pragmatics on the study of various types of statements (including references to belief), the importance of an integrative approach to the analysis of communicative processes and phenomena and the need for a total description of scientific dialogue as a socially and linguistically significant type of communication as well as by the necessity to study similarities and differences between national variants of the same type of communication.Methodology and sources. The methodological basis of the research is made up of the works by N. A. Alexandrova, E. G. Zadvornaya, L. N. Maslova, E. S. Troyanskaya, L. V. Slavgorodskaya, N. V. Solovyova and others devoted to the study of scientific dialogue. The source of the research material is made up transcripts of Russian and English scientific discussions in various fields of knowledge (from 2000 until now). The analysis is based on the structural, semantic and functional research methods.Results and discussion. The work reveals the structure of both the dictum and mode parts of references to belief (messages with an elliptical and expanded dictum as well as with an introductory, independent, subordinate and implicit modes), defines the pragmatic and expressive properties of various structural types of statements with the mode of belief (appellative and reflexive messages as well as more expressive and less expressive ones).Conclusion. The conclusion about the structural diversity of statements with the mode of belief (which indicates the importance of the phenomenon under study) as well as about some differences between Russian and English references to belief has been made.